Enhancing Crime Prevention and Patrol Efficiency Through Geospatial Policing Systems - Ririh Dewi Widowati (Universitas Negeri Semarang, 2025)
Geospatial policing has become a central innovation in modern law enforcement, utilizing geographic information systems (GIS), spatial analytics, and predictive mapping to identify crime patterns and guide strategic resource deployment. This study examines the operational impact, methodological foundations, and challenges of integrating geospatial intelligence into urban policing. A mixed-methods approach was applied, combining analysis of five years of crime data from three metropolitan jurisdictions with interviews involving 44 police officers, GIS analysts, and community representatives. Quantitative results show that geospatial mapping improves hotspot detection accuracy by 29% and reduces response time in high-crime areas by 17% when integrated with targeted patrol strategies. Spatial clustering techniques also enhanced officers’ situational awareness and improved crime prevention planning. Qualitative findings highlight challenges related to data quality, analytical skill gaps, and technological interoperability between GIS platforms and legacy police systems. The study concludes that geospatial policing significantly strengthens proactive law enforcement by generating spatially informed insights, optimizing patrol routes, and supporting evidence-based decision-making. Contributions to policing science include a comprehensive analytic framework for applying geospatial tools in operational contexts and recommendations for improving governance, training, and community transparency.